Flexible Usage and Interconnectivity of Diverse Cell Death Pathways Protect against Intracellular Infection - Marcel Doerflinger; Yexuan Deng; Paul G. Whitney; Ranja Salvamoser; Sven Engel; Andrew J. Kueh; Lin Tai; Annabell Bachem; Elise Gressier; Niall D. Geoghegan; Stephen Wilcox; Kelly L. Rogers; et al. (2020)
Programmed cell death contributes to host defense against pathogens. To investigate the relative importance of pyroptosis, necroptosis, and apoptosis during Salmonella infection, we infected mice and macrophages deficient for diverse combinations of caspases-1, -11, -12, and -8 and receptor interacting serine/threonine kinase 3 (RIPK3). Loss of pyroptosis, caspase-8-driven apoptosis, or necroptosis had minor impact on Salmonella control. However, combined deficiency of these cell death pathways caused loss of bacterial control in mice and their macrophages, demonstrating that host defense can employ varying components of several cell death pathways to limit intracellular infections. This flexible use of distinct cell death pathways involved extensive cross-talk between initiators and effectors of pyroptosis and apoptosis, where initiator caspases-1 and -8 also functioned as executioners when all known effectors of cell death were absent. These findings uncover a highly coordinated and flexible cell death system with in-built fail-safe processes that protect the host from intracellular infections.